Désigner l’épouse gallo-romaine. Essai d’analyse des pratiques épigraphiques autour d’uxor et de coniux. - Marianne Beraud (Genre & Histoire)
This work consists in a comparative study of the two conjugal terms ‘uxor’ and ‘coniux’ from epigraphic material in Gaul and in the Alps. This survey aims at understanding some aspects of the expression of domestic bonds and their terminology. The whole inscriptions reach a thousand tokens, the two wedded terms included. The available data related to vocabulary of wife are of a different nature according to the period and the country concerned. The analysis then focuses on the status of both civitates and their inhabitants. By examining Roman colonies and cities with well rooted ius latii, it is to be noticed an over representing of “uxores” and this carries on until the second half of the second century AC. Then, the “coniuges” dominate to the fourth century. On the other hand, a geographic area clearly stands out in the Rhodanian valley. In the colonies of Lugdunum and Vienna, the word ‘coniux’ is used as early as the first century AC, whereas the word ‘uxor’ is hardly used during the whole period. Another exception is the civitas of the Trevires in Gallia Belgica where wives are better called ‘coniuges’ as early as the beginning of the second century, while the term ‘uxor’ dominates the first century. By gathering, comparing and analyzing lexicon and formulas of the inscribed material, this thesis attempts to establish connections and similarities, and thereby reconstruct a common pattern of lexical practices to designate Gallo-Roman wife.